História da Caixa Geral de Depósitos, 1876-1910. - Lains, Pedro, author.
1 online resource.
Keywords: "This book examines the history of what became one of Portugal's largest banks, the Caixa Geral de Depósitos. The bank was founded in 1876 by the state to run public deposits, and evolved into a savings bank, catering for both public and private deposits. Its history goes beyond the history of banking, as it ties in with the role of the state in the banking sector and financial markets. The book weaves in and out of different political and international contexts, following the many changes of the Portuguese political regime and of its interactions with the national and international economy. The most important lesson from the study is that publicly owned institutions can compete successfully with the private sector when they simultaneously cater for the interests of policy makers as well as those of the public, in this case, the depositors. The history of the Caixa Geral de Depósitos therefore shows how the state of a peripheral economy is capable of successfully managing a large financial institution when the right set of incentives is in place. This work will be a valuable resource for researchers and students of financial and economic history at both the advanced undergraduate and postgraduate levels. It will also provide interesting insights for practitioners in the financial sector"--